Prenatal Exposure to Bisphenol A Analogues on Male Reproductive Functions in Mice. (21st March 2018) - Shi, Mingxin; Sekulovski, Nikola; MacLean, James A; Hayashi, Kanako
Abstract: This study was performed to examine whether prenatal exposure to bisphenol (BP) A analogues, BPE and BPS, negatively impacts male reproductive functions and testis development using mice as a model. CD-1 mice were orally exposed to control treatment (corn oil), BPA, BPE, and BPS (0.5, 20, or 50 µg/kg/day) from gestational day 11 (the presence of vaginal plug = 1) to birth. Although sperm counts were significantly reduced by BPA, BPE, or BPS on postnatal day (PND) 60, only BPE or BPS exposure remained low for sperm motility. Exposure to BPA, BPE, and BPS disrupted the progression of germ cell development, as morphometric analyses exhibited an abnormal distribution of the stages of spermatogenesis. Furthermore, BPS with a dose of 50 µg/kg/day increased a level of serum estradiol-17β in adult males. On PND12, BPE and BPS significantly increased TUNEL positive cells in neonatal testis, following disruption of the expression of apoptosis, autophagy, and oxidative stress-related factors. In addition, the expression of methyltransferases for DNA methylation and histone modification was also affected by prenatal exposure to BPA, BPE, or BPS in neonatal testis. These results suggest that prenatal exposure to BPE and BPS with physiologically relevant doses affects male reproductive functions probably due to spermatogenic defect in the developing testis.